Uso de um dispositivo LDR para o ensino de semicondutores fotoresistivos - Gonçalves, Edevânio João (2019)
In this qualitative research, we sought to build a Didactic Sequence (SD) that included a topic of Modern and Contemporary Physics (FMC) from the perspective of meaningful and contextualized learning.The theme addressed in SD was the photoresist semiconductors, starting from the problem question: what is the principle of activation and shutdown of public lighting through the use of a light sensor?The didactic sequence was prepared based on David Ausubel's Meaningful Learning theory and was applied in a public school to a group of 48 students enrolled in the third grade of high school.In the development of DS, different methodologies and tools were used.In groups of four students, they performed text interpretation, discussion and resolution of proposed exercises, use of computer simulations, handling of the experimental apparatus with the LDR device and multimeter.Through the analysis of the questionnaires it was possible to verify that the students acquired new knowledge, which allowed the verification of the social importance of science and a significant understanding of the behavior of a photoresist semiconductor material.